(untitled) (International journal of artificial intelligence, 2025)
This article explores the technology used in the construction of modern road pavements, particularly on highways. It addresses the issue of waste management, highlights the importance of improving recycling processes, and emphasizes the efficient use of recycled materials in road construction.